2019
DOI: 10.1016/j.fsigss.2019.10.033
|View full text |Cite
|
Sign up to set email alerts
|

Forensic parameters and genetic structure based on Y-chromosome short tandem repeats in Lesotho populations

Abstract: Lesotho is a landlocked country with approximately 2.2 million inhabitants. Over 97% of the population is represented by the Southern Sotho people (Sotho-Tswana group), followed by a number of minorities mostly from the Nguni language group. In this study we investigated the patterns of genetic variation and report genetic diversity, forensic parameters and novel allele variations in 938 unrelated Bantu males. Population pairwise comparisons identified high affinities between the Xhosa and the Vundle, while th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…A high level of allele diversity was observed among the studied populations as evident from the allelic richness (Ar) and haplotype and gene diversity values. These results agree with those obtained for Southern African populations (Lesaoana et al, 2019;Kasu et al, 2022) The Hausas harbor higher levels of allele richness or diversity than the other groups, which may be attributed to admixture, higher lineage diversity, marriage practices, or historical demographic processes. Allelic richness estimation is one of the various criteria for assessing within-and among-population genetic diversity and may also be used to estimate population evolutionary histories (Castric and Bernatchez, 2003;Ollivier and Foulley, 2005).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…A high level of allele diversity was observed among the studied populations as evident from the allelic richness (Ar) and haplotype and gene diversity values. These results agree with those obtained for Southern African populations (Lesaoana et al, 2019;Kasu et al, 2022) The Hausas harbor higher levels of allele richness or diversity than the other groups, which may be attributed to admixture, higher lineage diversity, marriage practices, or historical demographic processes. Allelic richness estimation is one of the various criteria for assessing within-and among-population genetic diversity and may also be used to estimate population evolutionary histories (Castric and Bernatchez, 2003;Ollivier and Foulley, 2005).…”
Section: Discussionsupporting
confidence: 89%
“…Duplications at the DYS626 locus are rare. The reported duplications at the DYS626 locus are unique and have not been encountered in previous studies with the same genotyping system in Lesotho (Lesaoana et al, 2019) and South African populations (Kasu et al, 2022). Ballantyne et al (2014) reported different duplications for this locus among Sub-Saharan (30,32 and 31,33),North African (31,32), admixed native American (30, 32), and European (29, 31) populations.…”
Section: Discussionmentioning
confidence: 48%
See 1 more Smart Citation
“…Alleles selected for the ladder were based on genotypic and sequence data captured previously in South African and Lesotho populations [15–20].…”
Section: Methodsmentioning
confidence: 99%
“…About 90% of the Burkinabe population speak Moore, Fulfulde and Dioula [1,3]. When genetic markers are applied to forensic cases of a certain population, forensic parameters for the population in question must be known [4]. However, no study on forensic parameters of a 29 Y-STR loci dataset has been done in BF to the best of our knowledge.…”
Section: Introductionmentioning
confidence: 99%